Laser-Induced Breakdown Spectroscopy (LIBS) Coupled with PCA and PLS for Identification and Adulteration Detection of Halal Meat Products - Ahmad, Khairunnas; Saiful, Saiful; Abdulmadjid, Syahrun Nur; Prasetyo, Siswoyo (UIN Sunan Gunung Djati Bandung, 2025)
Pork adulteration in halal meat is a significant issue in Indonesia, emphasizing the need for accurate methods to ensure product authenticity and protect consumers. This study aims to identify various meat products and evaluate the use of Laser-Induced Breakdown Spectroscopy (LIBS) in combination with Principal Component Analysis (PCA) and Partial Least Squares (PLS) for detecting meat adulteration. Samples were collected from various sources and analyzed using LIBS, with PCA used to distinguish meat species qualitatively and PLS to assess adulteration quantitatively. LIBS effectively distinguishes meat types, while PCA successfully identifies meat samples based on the intensity of the elemental compositions. PLS achieves high accuracy R2 > 0.99 in detecting pork adulteration in beef, buffalo, mutton, and chicken, surpassing single-line emission regression methods with low LOD (2.65%, 4.69%, 2.38%, and 3.41%) and LOQ (8.08%, 14.23%, 7.23%, and 10.34%) values. This study demonstrates that LIBS combined with PCA and PLS is a feasible and accurate method for identifying various meat types and detecting pork adulteration. The approach offers a reliable solution for addressing meat adulteration issues and ensuring halal application of LIBS with PCA and PLS for pork detection and quantification in halal meat product compliance.